THE INFLUENCE OF HALAL LABELING AND PRICE ON PURCHASING DECISIONS FOR GACOAN NOODLES (CASE STUDY OF MARELAN MUSLIM COMMUNITY) - Adibah, Zaidah; Lathief Ilhamy Nasution, Muhammad (JURNAL EKBIS, 2024)
The purpose of this study is to examine how halal labeling and price influence consumers' decision to purchase gacoan noodles (using the Marelan Muslim community as a case study). Halal label is usually very important for Muslim consumers when making a purchase. In addition, the price element is another aspect that is influential and closely related to it. Customers will also start looking for information about the products they need, including details about quality, price, production, reviews and other factors. Based on the types of needs and information findings they gather, consumers will use these to inform their purchasing decisions. With a sample size of 100 people, quantitative research will be used in this research design. The research findings show that consumers' decision to buy gacoan noodles is positively and significantly influenced by the halal label. Furthermore, the decision to buy gacoan noodles is positively and significantly influenced by the price variable. The low price of gacoan noodles encourages residents of Medan Marelan to purchase gacoan noodles in the lower middle class, so that the halal label owned by the company can have an impact on the decision to purchase gacoan noodles (case study on Marelan Muslim community).